A comparative template-switching cDNA approach for HTS-based multiplex detection of three viruses and one viroid commonly found in apple trees - Francisco Mosquera-Yuqui; Daniel Ramos-Lopez; Xiaojun Hu; Yu Yang; Joshua L. Mendoza; Emmanuel Asare; Joshua Habiger; Oscar P. Hurtado-Gonzales; Andres S. Espindola (Scientific Reports)
Abstract Exclusion is a keystone of integrated pest management to prevent the introduction of pathogens. U.S. plant quarantine programs employ PCR and high-throughput sequencing (HTS) to test imported plants for viruses and viroids of concern. Achieving a low limit of detection in any HTS protocol could be challenging. Following a template-switching cDNA amplification protocol, seven cDNA synthesis treatments were used to test simultaneously the relative abundance and coverage of the three most commonly latent RNA viruses found in apples: apple chlorotic leaf spot virus, apple stem grooving virus, and apple stem pitting virus, as well as the viroid apple hammerhead viroid. Amplified double-stranded cDNAs were subjected to library preparation using Nanopore SQK-DCS109 and Illumina Nextera XT, and sequenced with MinION and NextSeq2000, respectively. Treatments with oligo d(T)23-VN or its combination with random hexamers yielded the highest relative reads for viruses, while treatments containing the reverse primer pool produced more relative reads for AHVd. These treatments and random hexamers also generated the highest genome coverages, which were typically similar in both HTS workflows. However, relative abundances of viruses determined with SQK-DCS109 were up to 2.22-fold higher compared to Nextera XT. In contrast, Nextera XT yielded viroid reads 3.30-fold higher than SQK-DCS109. A framework of considerations for expanding this sensitive approach to other targets and crops is discussed.